Urgensi Sertifikasi Pendidik bagi Ustadz untuk Menjamin Mutu Pendidikan di Pondok Pesantren - Ahmad Syofiansyah (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper analyzes the urgency of teacher certification for ustadz in Islamic boarding schools (pondok pesantren) as a strategic effort to ensure educational quality, improve professionalism, and maintain the continuity of pesantren traditions. This issue is crucial due to the incompatibility between formal certification policies and the unique characteristics of pesantren education, which results in limited access, financial disparities, and philosophical differences. Without an inclusive policy framework, ustadz do not receive professional recognition on par with formal teachers, which threatens the quality and sustainability of pesantren education. This study uses a qualitative method with a policy study approach, supported by literature analysis and document review. Data was collected from various relevant regulations, research reports, and scientific publications on the issues of education and pesantren. The problem analysis was conducted using the USG (Urgency, Seriousness, Growth) theory and was supported by public policy theory, human capital theory, and the concepts of social justice and educational equity. The findings indicate that modifying the existing certification policy and developing a special track for pesantren are the two most viable and effective policy alternatives. The main recommendation is for the Minister of Religious Affairs to immediately issue a ministerial regulation that revises the teacher certification procedure to include a specific cluster for ustadz. This policy must recognize and give weight to sanad (chain of scholarly transmission), mastery of classical Islamic texts (kitab kuning), and teaching experience as key criteria.